INNOVATIVE ASPECTS OF MANAGEMENT IN THE PROCESS OF LOGISTIZATION IN BUSINESS ACTIVITIES - Galіuk I. B. (The actual problems of regional economy development, 2019)
The modern nature of entrepreneurial activity implies innovative behavior in the market. The degree of entrepreneurship is determined by the presence of a creative start in the activities of a businessman. And in this context, the question arises about the ratio in the motivational mechanism of entrepreneurship creative and self-interested aspects, that is, determining the orientation to profit. In a competitive market, the prerequisite for ensuring this ratio is the innovative component of the activity. At the same time, rational use of existing resources should be ensured, which is why the use of business process logistics as a basis for enhancing the competitiveness of an entrepreneurial structure is a must. The relatively new concept of innovative potential of business logistics is considered in the article in three aspects: as functional management, which ensures the distribution process of new products; as an innovative tool for managing economic flows in an enterprise, which is a more effective management technology than traditional methods of managing goods movement; as a manifestation of the process of improving the logistics infrastructure of the market for goods and services. The main directions of influence of the innovation factor in the business logistics system are determined, which determine the potential of its development, namely: the ability of business structures to generate, find, absorb and use knowledge determines their viability in the conditions of comprehensive uncertainty and volatility of the market environment; the process of informatization of economic flows of entrepreneurial activity on the basis of creation of information-logistic systems; modernization of the current institutional structure of the market; development of technological progress directly in the process of movement of goods; breaking many management stereotypes, combating corporate separatism and opportunism within business structures, reforming the system of purpose and interaction in business, instilling and cultivating new values in the economy.